Sustainable Use of Silk Vine Roots(S-VPR) as Low Cost Adsorbent for the Removal of Methylene Blue Dye from Its Aqueous Solution: - Mohammed, Rajoan; Mohamed, Abdussalam Salhin; Abusenaina , Ashraf M.; Khalifa, Fatima Abullrhman; Mohamed, Aze Salem (Scientific Journal for Faculty of Science-Sirte University, 2024)
This study examines the adsorption of methylene blue dye from an aqueous solution using silk vine roots derived from dairy powder. The adsorbent material was utilized in its natural state, without any chemical or physical treatment. The adsorption process was conducted under different conditions, including pH, adsorbent weight, initial dye concentration, and contact time at room temperature. The adsorption capacity exhibited an increase (49.9 mg/g), whereas the adsorbent weight and initial concentration increased until equilibrium was reached within 20 minutes. The adsorption process followed second-order kinetics and displayed compatibility with the Freundlich isotherm coefficient. It was determined to be a multilayer, heterogeneous adsorption process with a maximum adsorption capacity value (qe max 49.9 mg/g). Based on the results, it can be confirmed that wild dairy (silk vine) is capable of effectively adsorbing pollutants, such as the blue methylene dye.